2021
DOI: 10.3390/jcm10163477
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Patient-Centered Treatment Outcomes with Mandibular Overdentures Retained by Two Immediate or Conventionally Loaded Implants: A Randomized Clinical Trial

Abstract: This study aims to assess the treatment outcomes (functional and subjective) of mandibular overdentures retained on two implants with or without an immediate loading protocol. In this randomized clinical trial, twenty fully edentulous patients were treated with a mandibular two-implant-retained overdenture and a complete new maxillary denture. In half of the sample, the implants were loaded immediately by means of VulkanLoc® abutments after emplacement of the implant, but in the counterparts, these VulkanLoc® … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 44 publications
(62 reference statements)
4
13
1
Order By: Relevance
“…Focusing on satisfaction and quality of life, a clear improvement after prosthetic treatment was observed with satisfaction significantly higher among the IL than among the CL group ( Table 7 ), but not in terms of quality of life ( Table 8 ). In agreement with other studies [ 29 , 41 , 42 ] using the same assessment tools, the postoperative satisfaction and quality of life scores reported in the present study are higher than those observed among patients treated with two-implant retained overdentures. Specifically, the major improvements were observed among pain , functional limitation , and physical disability OHIP-dimensions ( Table 8 ), as found in other studies [ 29 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Focusing on satisfaction and quality of life, a clear improvement after prosthetic treatment was observed with satisfaction significantly higher among the IL than among the CL group ( Table 7 ), but not in terms of quality of life ( Table 8 ). In agreement with other studies [ 29 , 41 , 42 ] using the same assessment tools, the postoperative satisfaction and quality of life scores reported in the present study are higher than those observed among patients treated with two-implant retained overdentures. Specifically, the major improvements were observed among pain , functional limitation , and physical disability OHIP-dimensions ( Table 8 ), as found in other studies [ 29 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…In any case, the pre–post comparisons show that the occlusal area and the occlusal loading increase gradually from baseline conditions to fixed rehabilitation with PEEK-NFC ( Table 4 ). Nevertheless, the present study found greater areas of occlusion than that reported by Montero [ 29 ] (26.1 ± 15.7 mm 2 ); Baca et al [ 30 ] (21.0 ± 10.9) mm 2 ; Suzuki et al [ 31 ] (10.3 ± 5.2) mm 2 ; Iwaki [ 32 ] (7.0 ± 4.3) mm 2 , after using Dental PRESCALE in a comparable group of patients treated with two-implant overdentures [ 29 , 32 ] or conventional fixed rehabilitations [ 30 , 31 ]. These differences could be partially explained because of the distinct sensitivity of the pressure sheet (type 50 H, 97 μm thick) used in some studies [ 30 , 31 , 32 ] instead of the one used in the present study (MS type for medium pressure, 110 μm thick), but also because of the greater occlusal arrangement implemented by customized milled NFC crowns present on the present PEEK-NFC rehabilitations which is presumably better than that achieved when acrylic standardized teeth are used.…”
Section: Discussioncontrasting
confidence: 86%
See 3 more Smart Citations